Alcohol consumption and associations with sociodemographic and health-related characteristics in Germany: A population survey. (February 2022) - Garnett, Claire; Kastaun, Sabrina; Brown, Jamie; Kotz, Daniel
Highlights: Prevalence of hazardous drinking was 19.4% among adults in Germany between 2018 and 2019. Heavier levels of alcohol consumption were associated with being younger and male. Heavier levels of alcohol consumption were associated with having anxiety. Lower levels of alcohol consumption were associated with depression. Certain groups may benefit from targeted alcohol reduction policies and support. Abstract: Background: To assess the prevalence of ever-drinking and hazardous drinking among adults in Germany, and investigate the factors associated with level of alcohol consumption. Methods: Cross-sectional population survey of a representative sample of 11, 331 adults in Germany (2018 to 2019). The Alcohol Use Disorders Identification Test-Consumption (AUDIT-C) was used to define ever-drinking (AUDIT-C>=1), hazardous drinking (AUDIT-C>=5) and an overall AUDIT-C (alcohol consumption) score (from 0 to 12). Regression models were used to examine sociodemographic and health-related characteristics associated with AUDIT-C score. Results: The prevalence of ever-drinking and hazardous drinking was 84.7% (95% CI = 84.1–85.4) and 19.4% (95% CI = 18.6–20.1), respectively. The mean AUDIT-C score was 2.8 (SD = 2.16). AUDIT-C scores were independently positively associated with having medium (Badj  = 0.12, 95% CI = 0.02–0.21) and high (Badj  = 0.11, 95% CI = 0.01–0.21) educational qualifications (compared with low), monthly income (Badj  = 0.31 per €1, 000, 95% CI = 0.26–0.36), being a current smoker (Badj  = 0.94, 95% CI = 0.86–1.02), anxiety (Badj  = 0.26, 95% CI = 0.02–0.50), and living in North East (Badj  = 0.43, 95% CI = 0.29–0.58), North West (Badj  = 0.47, 95% CI = 0.39–0.55) and South East (Badj  = 0.79, 95% CI = 0.64–0.93) Germany (compared with South West), and negatively associated with age (Badj  = -0.17, 95% CI = -0.21- −0.13), being female (Badj  = -1.21, 95% CI = -1.28- −1.14) and depression (Badj  = -0.22, 95% CI = -0.43- −0.02). Conclusion: In a large, representative sample of adults in Germany, the majority were ever-drinkers and one fifth were hazardous drinkers. Higher alcohol consumption scores were associated with being younger, male, current smoker, of high socioeconomic position, anxiety, and not living in South West Germany, and lower scores were associated with depression. These groups may benefit from targeted alcohol reduction policies and support.